Educational intervention with serial album about pregnant women positioning for spinal anesthesia: randomized clinical trial - Sarah de Lima Pinto; Larissa Alves Sampaio; Nelson Miguel Galindo Neto; Paulo César de Almeida; Mirna Fontenele de Oliveira; Joselany Áfio Caetano (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To evaluate effectiveness of using educational intervention serial album to positioning pregnant women for spinal anesthesia. Method: Randomized clinical trial with 90 women casually assigned to control (CG) and intervention group (IG), in a maternity hospital located in Northeast region of Brazil. The primary endpoint was "achieve correct positioning to perform spinal anesthesia"; and secondary, "how number of spinal cord puncture attempts". Effectiveness was verified using the chi-square test, Fisher's exact test and likelihood ratio. Results: The positioning was correct in 37 women in each group. There was an association between women in control group remaining still, relaxing shoulders and flexing the spine; and women in intervention group should remain still and relax the shoulders; furthermore there was a statistical association achieved by correct positioning and the number of attempts to access the lumbar puncture. Conclusion: Educational intervention with serial album was effective and contributed to immobility and positioning of pregnant women. Brazilian Registry of Clinical Trials (RBR-3Z7SRD).